2021
DOI: 10.3389/fpls.2021.684626
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis 2′-O-Ribose-Methylation and Pseudouridylation Landscape of rRNA in Comparison to Human and Yeast

Abstract: Eukaryotic ribosome assembly starts in the nucleolus, where the ribosomal DNA (rDNA) is transcribed into the 35S pre-ribosomal RNA (pre-rRNA). More than two-hundred ribosome biogenesis factors (RBFs) and more than two-hundred small nucleolar RNAs (snoRNA) catalyze the processing, folding and modification of the rRNA in Arabidopsis thaliana. The initial pre-ribosomal 90S complex is formed already during transcription by association of ribosomal proteins (RPs) and RBFs. In addition, small nucleolar ribonucleopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 135 publications
(249 reference statements)
0
23
0
Order By: Relevance
“…In a recent study, 187 Ψ sites were discovered in Arabidopsis rRNA by genome-wide mapping ª 2022 The Authors. Plant Biotechnology Journal published by Society for Experimental Biology and The Association of Applied Biologists and John Wiley & Sons Ltd., 20, 1241-1256 (Sun et al, 2019). When comparing previously predicted Ψ sites in rRNA (Brown et al, 2003;Chen and Wu, 2009) with genomewide sequencing, the authors found evidence for 21 (of 32), 14 (of 25), and 1 (of 1) Ψ sites in large subunit (LSU) rRNA, small subunit (LSU), and 5.8S rRNA respectively (Sun et al, 2019).…”
Section: Pseudouridylation On Rrnamentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study, 187 Ψ sites were discovered in Arabidopsis rRNA by genome-wide mapping ª 2022 The Authors. Plant Biotechnology Journal published by Society for Experimental Biology and The Association of Applied Biologists and John Wiley & Sons Ltd., 20, 1241-1256 (Sun et al, 2019). When comparing previously predicted Ψ sites in rRNA (Brown et al, 2003;Chen and Wu, 2009) with genomewide sequencing, the authors found evidence for 21 (of 32), 14 (of 25), and 1 (of 1) Ψ sites in large subunit (LSU) rRNA, small subunit (LSU), and 5.8S rRNA respectively (Sun et al, 2019).…”
Section: Pseudouridylation On Rrnamentioning
confidence: 99%
“…Plant Biotechnology Journal published by Society for Experimental Biology and The Association of Applied Biologists and John Wiley & Sons Ltd., 20, 1241-1256 (Sun et al, 2019). When comparing previously predicted Ψ sites in rRNA (Brown et al, 2003;Chen and Wu, 2009) with genomewide sequencing, the authors found evidence for 21 (of 32), 14 (of 25), and 1 (of 1) Ψ sites in large subunit (LSU) rRNA, small subunit (LSU), and 5.8S rRNA respectively (Sun et al, 2019). A detailed comparison of all Ψ sites in Arabidopsis, human and yeast rRNA was described by Streit and Schleiff (Streit and Schleiff, 2021).…”
Section: Pseudouridylation On Rrnamentioning
confidence: 99%
See 3 more Smart Citations